C^*-algebras of labelled graphs II - simplicity results - Bates, Teresa; Pask, David (Mathematica Scandinavica, 2009)
We prove simplicity and pure infiniteness results for a certain class of labelled graph C^*-algebras. We show, by example, that this class of unital labelled graph C^*-algebras is strictly larger than the class of unital graph C^*-algebras.